2023
DOI: 10.3390/biomedicines11102823
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Two Multi-Tasking Approaches to Cognitive Training in Cardiac Surgery Patients

Irina Tarasova,
Olga Trubnikova,
Irina Kukhareva
et al.

Abstract: Background: The multi-tasking approach may be promising for cognitive rehabilitation in cardiac surgery patients due to a significant effect on attentional and executive functions. This study aimed to compare the neuropsychological changes in patients who have undergone two variants of multi-tasking training and a control group in the early postoperative period of coronary artery bypass grafting (CABG). Methods: One hundred and ten CABG patients were divided into three groups: cognitive training (CT) I (a post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…A magnetic resonance imaging study detected silent brain lesions after CABG in 20.1% of patients [37]. Recent research has indicated that approximately 60-70% of cardiac surgery patients experience postoperative cognitive dysfunction during the early postoperative period [10,37,38]. The BDNF serum levels decreased within the first 24 h of surgery in both the MTT group and the controls (p = 0.01 and p = 0.02, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A magnetic resonance imaging study detected silent brain lesions after CABG in 20.1% of patients [37]. Recent research has indicated that approximately 60-70% of cardiac surgery patients experience postoperative cognitive dysfunction during the early postoperative period [10,37,38]. The BDNF serum levels decreased within the first 24 h of surgery in both the MTT group and the controls (p = 0.01 and p = 0.02, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In the divergent task, the participants were asked to come up with creative ways to use ordinary objects (such as a ruler, glass, and a rope). All tasks were completed one by one, with a short period of rest and breaks from the balance platform [10].…”
Section: Multi-task Trainingmentioning
confidence: 99%
See 3 more Smart Citations